2021
DOI: 10.1002/mus.27328
|View full text |Cite
|
Sign up to set email alerts
|

Cortical excitability threshold can be increased by the AMPA blocker Perampanel in amyotrophic lateral sclerosis

Abstract: Introduction/Aims Cortical hyperexcitability is a feature of amyotrophic lateral sclerosis (ALS) and cortical excitability can be measured using transcranial magnetic stimulation (TMS). Resting motor threshold (MT) is a measure of cortical excitability, largely driven by glutamate. Perampanel, a glutamate α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) receptor blocker, is predicted to increase the cortical excitability threshold. This study aimed to evaluate TMS to functionally assess target engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Similar findings were reported in trials conducted in Parkinson disease 19 . In a recent study assessing the effect of perampanel on cortical excitability, administration of a single dose did not elicit any side effects 17 . Hence, a single dose of perampanel in ALS may be safe, but multiple doses over time, as in our study, appear to cause adverse events.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar findings were reported in trials conducted in Parkinson disease 19 . In a recent study assessing the effect of perampanel on cortical excitability, administration of a single dose did not elicit any side effects 17 . Hence, a single dose of perampanel in ALS may be safe, but multiple doses over time, as in our study, appear to cause adverse events.…”
Section: Discussionsupporting
confidence: 91%
“…16 In a recently published article, the authors studied the effect of a single dose of perampanel on cortical excitability and found a significant increase in motor threshold. 17 It was previously reported that administration of perampanel in patients with epilepsy is safe and that side effects were minor and dose-dependent. The side effects reported with an 8-mg/day dose include dizziness (32%), sleepiness (16%), fatigue (8%), irritability (7%), falls (5%), and imbalance (5%).…”
Section: Discussionmentioning
confidence: 99%
“…Non-competitive AMPA receptors have been demonstrated to confer protection against motor neuron death caused by excitotoxicity and 1,2,3,4-tetrahydro-6nitro-2,3-dioxo-benzo[f]quinoxaline-7-sulfonamide disodium salt (NBQX)-the selective AMPA/kainate receptor antagonist, as well as prolong the survival of transgenic SOD1 G93A mutant mice [141,142]. Moreover, in other studies, perampanel, an FDA-approved noncompetitive AMPA receptor antagonist to manage epilepsy, has prevented ALS-like progressive motor dysfunction in conditional ADAR2 knockout mice and increased the cortical excitability threshold [143,144]. However, with the exception of an improvement in the manual muscle testing score, perampanel did not effectively inhibit disease progression in a recent phase 2 clinical trial on sporadic ALS patients [145,146].…”
Section: Promising Therapy Targeting Rna Editing Dysregulation In Neurological Diseasesmentioning
confidence: 99%
“…In amyotrophic lateral sclerosis (ALS), a neurodegenerative disease in which the motor neurons are the main loci of disease activity, the suppression of hyperexcitability has been investigated as a therapeutic strategy [ 15 , 16 , 17 ]. Clinical trials using antiepileptic drugs has already been completed [ 18 , 19 , 20 , 21 , 22 ]. In Parkinson disease, the possibility of disease-modifying therapy using Ca 2+ channel blockers that inhibit neuronal excitability has been suggested [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Parkinson disease, the released dopamine itself may be chemically responsible for inducing oxidative stress and predisposing the brain to neurodegeneration [ 13 , 14 ]. In contrast, glutamate is widely distributed in the brain and acts as an excitatory neurotransmitter in ALS [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Glutamate acts on N-methyl-D-aspartate (NMDA) receptors at postsynaptic sites, but excitotoxicity, caused by excessive glutamate release, leads to neuronal death.…”
Section: Introductionmentioning
confidence: 99%